Correlation of physiological and productive parameters of cowpea under organic fertilization - Santiago da Costa, Rafael; de Souza Silva, Johny; Queiros Vieira, Júlia; Moreira Pinho, Beatriz; Alves da Silva, Bruna; Araujo Crisostomo, Lindbergue; de Melo Braga, Marilena; Oliveira Mesquita, Rosilene (Revista Ciência Agronômica, 2023)
The work was intended to evaluate the effect of different organic compounds originating from the mixture of agroindustrial and urban wastes, as well as their doses in the physiology and production of cowpea. The experiment was conducted under a randomized block design, in a 4 x 5 + 2 factorial arrangement, with four organic fertilizers (3 composed obtained from of sewage sludge, green coconut shell, carnauba butt; and sewage sludge biochar), five doses (20, 40, 60, 80 and 100 t ha-1) and two additional treatments (without fertilization and mineral fertilization).